2006
DOI: 10.1016/j.urology.2006.08.1063
|View full text |Cite
|
Sign up to set email alerts
|

Vesicourethral anastomosis during endoscopic extraperitoneal radical prostatectomy: A prospective comparison between the single-knot running and interrupted technique

Abstract: Both techniques provide satisfactory and similar functional results. However, because of its simplicity and shorter operative time, the single-knot running technique appears preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 30 publications
1
28
3
2
Order By: Relevance
“…Studies have shown that a majority (79 to 95%) of patients undergoing radical prostatectomy do not have a urine leak by cystogram seven days postoperatively (13)(14)(15). By 15 to 21 days after surgery, nearly 100% of patients do not have a urinary leak at the UVA (13,16). The type or number of sutures used has not seemed to affect urinary leak rates, suggesting that the most important factor in a leak-free UVA is good tissue approximation and an intraoperative watertight closure.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a majority (79 to 95%) of patients undergoing radical prostatectomy do not have a urine leak by cystogram seven days postoperatively (13)(14)(15). By 15 to 21 days after surgery, nearly 100% of patients do not have a urinary leak at the UVA (13,16). The type or number of sutures used has not seemed to affect urinary leak rates, suggesting that the most important factor in a leak-free UVA is good tissue approximation and an intraoperative watertight closure.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective comparison study showed that there were no differences in extravasation rate, catheterization time and occurrence of anastomotic strictures between the two types of techniques, but the running technique took less operative time and had a lower difficulty score [5]. Therefore, in this study, we developed an economical porcine model for LESS UVA training by using the running suture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, anastomotic urinary leakage and bladder neck strictures may result in urinary retention, pelvic abscess and a delayed return of continence, complications which commonly necessitate secondary procedures [3,5,6]. In the quest for an optimal VUA, several modifications have been previously described including interrupted and running sutures [7,8,9,10,11]. A running suture is faster and easier to perform, with fewer knots required than the interrupted one [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the quest for an optimal VUA, several modifications have been previously described including interrupted and running sutures [7,8,9,10,11]. A running suture is faster and easier to perform, with fewer knots required than the interrupted one [10]. The Van Velthoven VUA is a commonly used technique due to its proven feasibility and safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation